Bioaccumulation of metals and granular sludge development in a newly-inoculated high rate anaerobic reactor. (September 2018) - Cuff, Graham; Turcios, Ariel E.; Mohammad-pajooh, Ehsan; Kujawski, Olaf; Weichgrebe, Dirk; Rosenwinkel, Karl-Heinz
Abstract: For treatment of wastewater from soft drink production, a full scale (546 m 3 ) expanded granular sludge bed (EGSB) reactor was inoculated with granular sludge previously used to treat wastewater from paper and food processing industries. During startup and subsequent phases, there were significant changes observed in granule composition, performance, and population distribution. Microbial, compositional and functional development of granular sludge during a six month time period immediately following inoculation was investigated. Reaction kinetics and fluorescence in situ hybridization (FISH) analysis were used to describe population dynamics and evolution of methanogens and fermentative microbes within the granules. Bioaccumulation of elements was quantified and analyzed statistically with respect to operational parameters; calcium and sulfate deficiencies in the new wastewater likely contributed to granule disintegration and eventual reactor failure. Second generation granules formed from the novel conditions exhibited characteristics from multiple granulation models. Highlights: Bioaccumulation of metals in granular sludge was studied under new substrate loads. Element deficiency (Ca and S) most likely caused granule disintegration. Second generation granules exhibited combined layered and cluster structures. After six months of operation under new substrate, granules reached stable phase.